An Experimental Study on Dielectric Relaxor Behavior of the System (Pb1-xBax ) ZrO3 (x = 0.25, 0.30, 0.35) Ceramics - Subedi, Ratna Mani (Himalayan Physics, 2011)
Not available. Key words: Dielectric Relaxor Behavior The Himalayan Physics Vol.1, No.1, May, 2010 Page: 73-76 Uploaded Date: 29 July, 2011